The 'Day Zero' Cape Town drought and the poleward migration of moisture corridors. (17th December 2018) - Sousa, Pedro M; Blamey, Ross C; Reason, Chris J C; Ramos, Alexandre M; Trigo, Ricardo M
Abstract: Since 2015 the greater Cape Town area (∼3.7 million people) has been experiencing the worst drought of the last century. The combined effect of this prolonged dry period with an ever-growing demand for water culminated in the widely publicized 'Day Zero' water crisis. Here we show how: (i) consecutive significant decreases in rainfall during the last three winters led to the current water crisis; (ii) the 2015–2017 record breaking drought was driven by a poleward shift of the Southern Hemisphere moisture corridor; (iii) a displacement of the jet-stream and South Atlantic storm-track has imposed significantly drier conditions to this region. Decreasing local rainfall trends are consistent with an expansion of the semi-permanent South Atlantic high pressure, and reflected in the prevalence of the positive phase of the Southern Annular Mode. Large-scale forcing mechanisms reveal the intensification and migration of subtropical anticyclones towards the mid-latitudes, highlighting the link between these circulation responses and the record warm years during 2015–2017 at the global scale.